Integration of Transcriptome and Metabolome Reveals the Formation Mechanism of Red Stem in Prunus mume - Qiu, Like; Zheng, Tangchun; Liu, Weichao; Zhuo, Xiaokang; Li, Ping; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (Frontiers in Plant Science, 2022)
Prunus mume var. purpurea, commonly known as "Red Bone", is a special variety with pink or purple-red xylem. It is famous due to gorgeous petals and delightful aromas, playing important roles in urban landscaping. The regulation mechanism of color formation in P. mume var. purpurea stem development is unclear. Here, we conducted a comprehensive analysis of transcriptome and metabolome in WYY (‘Wuyuyu’ accession, red stem) and FLE (‘Fei Lve’ accession, green stem), and found a total of 256 differential metabolites. At least fourteen anthocyanins were detected in WYY, wherein cyanidin 3,5-O-diglucoside and peonidin3-O-glucoside were significantly accumulated through LC-MS/MS analysis. Transcriptome data showed that the genes related to flavonoid-anthocyanin biosynthesis pathways were significantly enriched in WYY. The ratio of dihydroflavonol 4-reductase (DFR) and flavonol synthase (FLS) expression levels may affect metabolic balance in WYY, suggesting a vital role in xylem color formation. In addition, several transcription factors were up-regulated, which may be the key factors contributing to transcriptional changes in anthocyanin synthesis. Overall, the results provide a reference for further research on the molecular mechanism of xylem color regulation in P. mume and lay a theoretical foundation for cultivating new varieties.